From Bucket To Plate: Training On Making Budikdamber Media For Youth - Prasetyo, Agung; Mahananto; Arbianti (Universitas Tunas Pembangunan Surakarta, 2025)
This activity was to give training for youth about how to make an innovative and sustainable method for integrating fish and vegetable cultivation using minimal space. The training aimed to enhance participants' understanding and skills in material selection, installation making, waste utilization, and aquaponic farming techniques. Initially, participants had a poor comprehension of these concepts, with an understanding score of 52.5 (Category E). However, after completing hands-on training, their scores improved to the 52-63 range (Category B), demonstrating significant progress. The training covered essential aspects such as selecting durable and cost-effective materials, constructing efficient Budikdamber installations, repurposing plastic cup waste for hydroponic plant cultivation, and balancing the aquatic ecosystem for optimal fish and vegetable growth. The results highlight the effectiveness of practical education in fostering sustainable agricultural practices and reducing environmental impact. These findings emphasize the potential of Budikdamber systems in enhancing food security, resource efficiency, and economic opportunities for communities.